Study Some Mechanical Properties of Binary Polymer Blends Fabricated by Friction Stir Processing (Journal of University of Babylon for Engineering Sciences, 2018)
Friction stir processing (FSP) is a promising technique to improve the mechanical properties of the polymer blends surface with retainment of bulk properties, in this work an attempt was done to add different ratios of polypropylene (PP), styrene acrylonitrile (SAN) and polyvinyl chloride (PVC) as a second material to the matrix plate high density polyethylene (HDPE). Mechanical properties were estimated for hardness and tensile tests were carried out to assess the performance of friction stir processed to prepared the binary polymers blends (HDPE: PP), (HDPE: SAN) and (HDPE: PVC) at depth 3 mm from the surface of (HDPE) plate. The results of the tests showed that the best values of the tensile strength, young modulus and hardness, it was obtained when adding the ratio of (15%) of the (PVC) to matrix (HDPE). The friction stir processing technique was successfully used to improve the mechanical properties of polymer surface. In view of the foregoing, it can be concluded that the friction stir processing technique, can be utilizing to repair the cracks and imperfections that are formed in polymeric materials.